Detection of Mycobacterium bovis in Organs of Slaughtered Cattle by DNA-Based Polymerase Chain Reaction and Ziehl-Neelsen Techniques in Bauchi State, Nigeria - Sa'idu, A. S. (J Vet Med, 2015)
Bovine tuberculosis is a chronic, infectious, and contagious zoonotic disease of domestic animals, wild animals, and humans. It also poses a public health threat and economic losses. This study was aimed at determining the prevalence of bovine tuberculosis in slaughtered cattle, based on PM meat inspection, Ziehl-Neelsen staining, and PCR techniques in Bauchi State, Nigeria. A Prospective study was conducted on 800 cattle slaughtered in the three Zonal abattoirs of Bauchi State, Nigeria. One hundred and twenty (15%) tissues from different organs had suspected bTB lesions at PM. Out of the samples examined 35 (29.2%) were AFB positive by ZN and 10 (8.3%) were confirmed positive for M. bovis by PCR, with an overall prevalence of 29.16% and 8.33%, respectively. Female had a higher prevalence rate than male cattle at 16.66% and 12.5 % by ZN and 5.00% and 3.33% by PCR, respectively (P>0.05, χ (2) = 0.218). However, there was a statistically significant association (P<0.05, χ (2) = 7.002) between detection of bTB and the age of cattle. ZN revealed that cattle aged 6 years and above had the highest number of positive bTB cases 67.9%, while cattle aged 3–5 years had the lowest 14.81%. PCR technique revealed that the cattle aged 6 and above years also had the highest percentage positive M. bovis cases of 22.84%, whereas cattle aged 3–5 years had the lowest and the overall prevalence rate of 8.33%. The study found a high infection rate of bTB among cattle and majority of the lesions 54.2% were from lungs. The prevalence of bTB was higher in Bauchi metropolitan abattoir which supplies larger population of the state with beef.